Can soluble urokinase plasminogen receptor predict outcomes after cardiac surgery?. (24th November 2020) - Schultz-Swarthfigure, Chase T; McCall, Philip; Docking, Robert; Galley, Helen F; Shelley, Benjamin
Abstract: OBJECTIVES: Soluble urokinase plasminogen activator receptor (suPAR) is a biomarker that has been implicated in several cardiac pathologies and has been shown to be elevated in critically ill populations. We measured plasma suPAR in a cohort of cardiac surgical patients to evaluate its ability to predict prolonged intensive care unit (ICU) and hospital length of stay and development of complications following surgery. We compared suPAR against EuroSCORE II and C-reactive protein (CRP). METHODS: Ninety patients undergoing cardiac surgery were recruited with samples taken preoperatively and on postoperative days 1, 2 and 3. suPAR was measured using enzyme-linked immunosorbent assay. Area under the receiver operator curve (AUROC) was used to test predictive capability of suPAR. Comparison was made with EuroSCORE II and CRP. RESULTS: suPAR increased over time ( P < 0.001) with higher levels in patients requiring prolonged ICU and hospital stay, and prolonged ventilation ( P < 0.05). suPAR was predictive for prolonged ICU and hospital stay, and prolonged ventilation at all time points (AUROC 0.66–0.74). Interestingly, this association was also observed preoperatively, with preoperative suPAR predicting prolonged ICU (AUROC 0.66), and hospital stay (AUROC 0.67) and prolonged ventilation (AUROC 0.74). The predictive value of preoperative suPAR compared favourably to EuroSCORE II and CRP. CONCLUSIONS: suPAR increases following cardiac surgery and levels are higher in those who require prolonged ICU stay, prolonged hospital stay and prolonged ventilation. Preoperative suPAR compares favourably to EuroSCORE II and CRP in the prediction of these outcomes. suPAR could be a useful biomarker in predicting outcome following cardiac surgery, helping inform clinical decision-making. Clinical registration: West of Scotland Research Ethics Committee Reference: 12/WS/0179 (AM01). Abstract : Patients undergoing cardiac surgery are at the risk of multisystem postoperative complications [1], resulting in the prolongation of intensive care unit (ICU) admission [2] and hospital stay [3].